A Meta-Analysis of Emotional Evidence for the Biophilia Hypothesis and Implications for Biophilic Design - Gaekwad, Jason S.; Sal Moslehian, Anahita; Roös, Phillip B.; Walker, Arlene (Frontiers in Psychology, 2022)
The biophilia hypothesis posits an innate biological and genetic connection between human and nature, including an emotional dimension to this connection. Biophilic design builds on this hypothesis in an attempt to design human-nature connections into the built environment. This article builds on this theoretical framework through a meta-analysis of experimental studies on the emotional impacts of human exposure to natural and urban environments. A total of 49 studies were identified, with a combined sample size of 3201 participants. The primary findings indicated that exposure to natural environments had a medium to large effect on both increasing positive affect and decreasing negative affect. This finding supported the anticipated emotional dimension of the biophilia hypothesis and lends credibility to biophilic design theory. Evidence was revealed in support of the affective/arousal response model. Immersion in environments indicated a larger effect size than laboratory simulation of environments. Methodological recommendations for future experimental research were few, however the Positive and Negative Affect Schedule (PANAS) outcome measure was recommended as a measure of both positive and negative affect for further studies. A combination measurement of stress related outcome variables was proposed to further explore the affective/arousal response model and its potential relationship to the biophilia hypothesis. The meta-analysis provides evidence for fundamental theories regarding human-nature connection, while revealing gaps in current knowledge.